2007
DOI: 10.1016/j.schres.2006.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sensorimotor gating and clinical improvement in acutely ill schizophrenia patients

Abstract: It has been suggested that sensorimotor gating deficits as indexed by prepulse inhibition (PPI) of the acoustic startle reflex represent an endophenotypic marker of psychotic conditions such as schizophrenia (SCZ). This hypothesis has been questioned as several studies have found that PPI levels change with improvement in symptoms and are responsive to medications. We tested PPI in a sample of acutely decompensated schizophrenia patients who were re-tested after 2 weeks of hospital treatment. PPI was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 31 publications
6
23
0
1
Order By: Relevance
“…Furthermore, no differences were found between CON and SCZ or SCZ-FAM for habituation (Figure 1d). This finding is in agreement with many (Ludewig et al, 2002; Perry et al, 2002; Wynn et al, 2004; Braff et al, 2005; Quednow et al, 2006; Kunugi et al, 2007; Minassian et al, 2007; Quednow et al, 2008a), but not all (Parwani et al, 2000; Ludewig et al, 2003; Meincke et al, 2004; Takahashi et al, 2008) previous reports in schizophrenia populations.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, no differences were found between CON and SCZ or SCZ-FAM for habituation (Figure 1d). This finding is in agreement with many (Ludewig et al, 2002; Perry et al, 2002; Wynn et al, 2004; Braff et al, 2005; Quednow et al, 2006; Kunugi et al, 2007; Minassian et al, 2007; Quednow et al, 2008a), but not all (Parwani et al, 2000; Ludewig et al, 2003; Meincke et al, 2004; Takahashi et al, 2008) previous reports in schizophrenia populations.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, racial background was a significant covariate in the present analysis, with Caucasian subjects having higher startle magnitudes than African-American subjects, a finding that supports earlier studies on this topic (Brown et al, 2006; Hasenkamp et al, 2008). No differences between CON and SCZ or SCZ-FAM were detected in this study for startle magnitude (Figure 1b), in line with previous findings (Braff et al, 1992; Cadenhead et al, 2000; Parwani et al, 2000; Ludewig et al, 2002; Perry et al, 2002; Wynn et al, 2004; Braff et al, 2005; Swerdlow et al, 2006; Takahashi et al, 2008), but see (Quednow et al, 2006; Minassian et al, 2007). In general, comparable results were found for initial startle reactivity, with heritability at 54%, and no differences between groups.…”
Section: Discussionsupporting
confidence: 93%
“…Most importantly, although impaired startle PPI is shared by several neuropsychiatric diseases, it is consistently observed in schizophrenia, in which it is believed to be an index of the deficient sensorimotor gating underpinning sensory flooding and cognitive fragmentation (Braff and Geyer, 1990;Braff et al, 1992Braff et al, , 2001Braff et al, , 2007Swerdlow et al, 1994Swerdlow et al, , 2006Minassian et al, 2007). Rothstein et al (2005) showed that CEF robustly stimulates GLT-1 expression, but not that of the other glutamate transporters, through increased GLT-1 gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The startle session was similar to previous methodology (Ahmari, Risbrough, Geyer, & Simpson, 2012; Minassian et al, 2007), beginning with a 5-minute acclimation period of 70 dB(A) white noise followed by four blocks of trials. The first and last blocks consisted of five pulse-alone trials of 40 msec 115-dB(A) startle stimuli.…”
Section: Methodsmentioning
confidence: 99%